The Effect of Job Satisfaction and Organizational Commitment on Employee Performance with OCB as the Intervening Variables - Bagas Kristian; Agatha Ferijani (Soegijapranata Catholic University, 2020)
This study aims to describe and analyze the effect of job satisfaction and organizational commitment on employee performance with OCB as the intervening variable. In this study the data collection technique was questionnaire in which the respondents were selected using purposive sampling technique. Based on descriptive analysis, the results conclude that the level of job satisfaction is high, organizational commitment is high, OCB is very high, and employee performance is also very high. Job satisfaction and organizational commitment respectively have positive and significant effect on OCB. OCB has a positive and significant effect on employee performance. Job satisfaction and organizational commitment also respectively have positive and significant effect on employee performance. Job satisfaction and organizational commitment have positive and significant effect on performance with OCB as the intervening variable.